First pselaphine beetles from Xinjiang Uygur Autonomous Region, China (Coleoptera: Staphylinidae: Pselaphinae) - Yin, Zi-Wei (Zootaxa, 2022)
The genus Brachygluta Thomson, 1859 and two widely distributed Central Asian species, B. iranica (Saulcy, 1876) and Trissemus melinus (Solsky, 1870), are newly recorded from China (Xinjiang). A diagnosis, illustrations of the habitus and morphological details of both species, and a redescription of T. melinus is provided.